2017
DOI: 10.1111/ijcs.12365
|View full text |Cite
|
Sign up to set email alerts
|

Communicating social support during crises at the farmers’ market: A social exchange approach to understanding customer‐farmer communal relationships

Abstract: This ethnographic research explores how the social support developed between customers and farmers at a farmers’ market creates an overall culture of community support that bolsters farmers’ viability during times of crisis and ensures that consumers will have access to healthy, high quality local food. This includes the ways customers provide a general culture of support for local farmers, as well as specific acts of support during times of crisis. It also examines the ways farmers support customers through s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 57 publications
2
38
0
Order By: Relevance
“…Aligned with this argument, recent empirical studies have demonstrated the positive and attenuating effect of new and innovative logics of production and supply, networks and community-based responses to crises (e.g. Blättel-Mink et al, 2017;Garner, 2017;Lindlbom & Lindlbom, 2017).…”
Section: Consumers' Coping Strategiesmentioning
confidence: 94%
See 1 more Smart Citation
“…Aligned with this argument, recent empirical studies have demonstrated the positive and attenuating effect of new and innovative logics of production and supply, networks and community-based responses to crises (e.g. Blättel-Mink et al, 2017;Garner, 2017;Lindlbom & Lindlbom, 2017).…”
Section: Consumers' Coping Strategiesmentioning
confidence: 94%
“…Different aspects of crises and consumption are being examined including the changing process of household budget allocations (Du & Kamakura, 2008;Kamakura & Du, 2012), consumer price consciousness (Hampson & McGoldrick, 2017), calculative price behavior (Berdysheva & Romanova, 2017), the role of private labels and discount stores (Puelles et al, 2016;Lamey, Deleersnyder, Dekimpe, & Steenkamp, 2007), adaptive shopping patterns (Hampson & McGoldrick, 2013), consumers' money attitudes in the postrecession economy (Hampson et al, 2018), social and political discourses (Alonso, Rodríguez, & Rojo, 2015, media discourses (Vihalemm, Keller, & Pihu, 2016), ethnocentric consumption (Lekakis, 2017), social innovation and community-based responses (Blättel-Mink et al, 2017), communal exchange and social resilience (Garner, 2017) and collaborative consumption (Lindlbom & Lindlbom, 2017).…”
Section: Crises Business Dynamics and Consumptionmentioning
confidence: 99%
“…Two articles in this issue, one by Garner () and the other by Blättel‐Mink, Boddenberg, Gunkel, Schmitz, and Vaessen () explain the innovative aspect of crisis by presenting two cases of agricultural exchange that alter consumer‐producer relationships. Blättel‐Mink et al .…”
Section: Contributions Of the Papers Of The Special Issuementioning
confidence: 99%
“…Sustainability is a linchpin of many farmers’ markets, and some argue that sustainability is a reason why direct, alternative markets have grown recently in the United States (US), Canada, New Zealand, and the UK (Betz & Farmer, ; Brown, ; Carey, Bell, Duff, Sheridan, & Shields, ; Guthrie, Guthrie, & Lawson, ; Lawson, Guthrie, Cameron, & Fischer, ; Smithers, Lamarche, & Joseph, ; USDA, , ). Customers attend markets for many reasons: to get fresh food (Alonso & O'Neill, ; Brown, ; McNeill & Hale, ; Trobe, ), to encourage sustainable farming practices (Alkon, ; Garner, ), to support local farms economically (Brown & Miller, ; Lyson, Gillespie, & Hilchey, ), to build community ties (Feagan & Morris, ), have a more personal exchange (Garner, ; Robinson & Hartenfeld, ), and express their morality or ethics (Garner, ; McEachern, Warnaby, Carrigan, & Szmigin, ).…”
Section: Introductionmentioning
confidence: 99%
“…While supporting small local farms sounds logical, the size of the farm matters less than the agricultural methods used (Forssell & Lankoski, 2015). Even still, marketing and selling sustainably grown products may offer a competitive advantage (Wolf et al, 2005) over grocery store food products because this strategy allows farmers the opportunity to increase consumers' trust in in their operation through strengthened relationships and transparency (Feagan & Morris, 2009;Garner, 2017;Hunt, 2007).…”
mentioning
confidence: 99%